2021
DOI: 10.1016/j.neuron.2021.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and inhibitory action of hippocampal axo-axonic cells during behavior

Abstract: The axon initial segment of hippocampal pyramidal cells is a key subcellular compartment for action potential generation, under GABAergic control by the ''chandelier'' or axo-axonic cells (AACs). Although AACs are the only cellular source of GABA targeting the initial segment, their in vivo activity patterns and influence over pyramidal cell dynamics are not well understood. We achieved cell-type-specific genetic access to AACs in mice and show that AACs in the hippocampal area CA1 are synchronously activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 86 publications
11
71
1
Order By: Relevance
“…33,39,40 Similar trends were found on the time scale of seconds, during smaller activity fluctuations within behavioral states: while PVBC activity is strongly positively correlated to pyramidal cell activity, AAC activity is only weakly correlated and CCKBC activity is clearly negatively correlated (Figure 1c). 32,33 This latter observation is especially surprising because previous reports (lacking specific CCKBC labeling) suggested that interneuron activity typically scales positively with network activity, both in control and epileptic brains. Positively scaled, also known as balanced inhibition, contributes to stabilizing network dynamics across a wide range of activity levels.…”
Section: Distinct Activity Patterns Of Perisomatic Interneurons In Vivosupporting
confidence: 75%
See 3 more Smart Citations
“…33,39,40 Similar trends were found on the time scale of seconds, during smaller activity fluctuations within behavioral states: while PVBC activity is strongly positively correlated to pyramidal cell activity, AAC activity is only weakly correlated and CCKBC activity is clearly negatively correlated (Figure 1c). 32,33 This latter observation is especially surprising because previous reports (lacking specific CCKBC labeling) suggested that interneuron activity typically scales positively with network activity, both in control and epileptic brains. Positively scaled, also known as balanced inhibition, contributes to stabilizing network dynamics across a wide range of activity levels.…”
Section: Distinct Activity Patterns Of Perisomatic Interneurons In Vivosupporting
confidence: 75%
“… 32 AACs are recruited during theta-, but not during ripple oscillations. 33 , 39 , 40 Similar trends were found on the time scale of seconds, during smaller activity fluctuations within behavioral states: while PVBC activity is strongly positively correlated to pyramidal cell activity, AAC activity is only weakly correlated and CCKBC activity is clearly negatively correlated ( Figure 1c ). 32 , 33 …”
Section: Distinct Activity Patterns Of Perisomatic Interneurons ...supporting
confidence: 71%
See 2 more Smart Citations
“…On the one hand, we very much need cellular-based network models to help us untangle the various facets of the interacting dynamics of the network system that produces theta and gamma rhythms and their coupling as this cannot come from experiments alone. Simply identifying and targeting the many different inhibitory cell types during ongoing behaviours and rhythmic activities is an immense, ongoing experimental challenge that is extremely laborious [36][37][38] . On the other hand, the presence of nonlinearity, high-dimensionality and degeneracy in detailed models makes it difficult to extract explicit mechanisms.…”
Section: Introductionmentioning
confidence: 99%